2016
DOI: 10.1186/s13071-016-1608-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new tick species, Ixodes collaris n. sp. (Acari: Ixodidae), from bats (Chiroptera: Hipposideridae, Rhinolophidae) in Vietnam

Abstract: BackgroundIn a recent study on ixodid bat ticks from Eurasia, a high genetic difference was found between Ixodes vespertilionis from Europe and Vietnam. Accordingly, it was proposed that I. vespertilionis is a species complex, with at least one additional, hitherto undescribed species. The aim of the present study was to investigate the morphology of bat ticks from Vietnam and to assess their taxonomic status in comparison with those collected in Europe.FindingsIxodid bat ticks (two females and two nymphs) col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…With the morphological characters, high resolution pictures and drawings provided in the present study, descriptions of all stages of I. collaris are now complete. Adding to already reported genetic differences between I. vespertilionis , I. collaris , I. ariadnae and I. simplex [ 1 ], these ixodid bat tick species show different morphology in all stages, as shown formerly for females and nymphs [ 2 ] and here for males and larvae.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…With the morphological characters, high resolution pictures and drawings provided in the present study, descriptions of all stages of I. collaris are now complete. Adding to already reported genetic differences between I. vespertilionis , I. collaris , I. ariadnae and I. simplex [ 1 ], these ixodid bat tick species show different morphology in all stages, as shown formerly for females and nymphs [ 2 ] and here for males and larvae.…”
Section: Discussionsupporting
confidence: 72%
“…Accordingly, I. collaris Hornok, 2016, has been described, based on material from the intermediate horseshoe bats ( Rhinolophus affinis ) in Vietnam. However, the description of this new species was based only on the female and the nymph [ 2 ], because at that time male bat ticks were not seen on cave walls and larvae could not be collected from the only known host species.…”
Section: Introductionmentioning
confidence: 99%
“…While neither live virus nor nucleic acid of CCHFV has been detected from bats, serologic evidence suggests past infection of populations of bats across a diverse geographic range [15,16,17]. Further, bats are often parasitized by both soft and hard ticks, which occupy a diverse range of ecological niches in endemic countries [18,19,20]. A 2016 seroprevalance study by Müller and colleagues examining 16 African bat species ( n = 1,135) found that the prevalence of antibodies against CCHFV was much higher in cave-dwelling bats (3.6%–42.9%, depending on species) than foliage-living bats (0.6%–7.1%) [15].…”
Section: Members Of the Order Bunyaviralesmentioning
confidence: 99%
“…A number of hematophagous arthropods feed on bats, including bat flies (genera Nycteribiidae and Streblidae ), bat bugs and bed bugs (family Cimicidae ), and ticks (families Argasidae and Ixodidae ) [18,20,21,167,168,169,170,171,172]. Viruses of medical and veterinary significance have also been isolated from these arthropods [21,173,174,175].…”
Section: Relationships Between Bats and Arthropodsmentioning
confidence: 99%
“…According to recent studies ticks fauna comprised of 939 species segregated into three families Ixodidae (727 species), Nuttalliellidae (1 species) and Argasidae (211 species) worldwide. Neotropical region approximately contain one fourth of these ticks species (Labruna et al 2016;Hornok et al, 2016;Apanaskevich and Bermúdez, 2017;Ash et al, 2017;Nava et al, 2017;Chitimia-Dobler et al, 2017). In tropical regions the most significant hard ticks which parasitize livestock belong to genera Hyalomma, Amblyomma and Rhipicephalus (Manan and Zabita-Khan, 2007).…”
Section: Introductionmentioning
confidence: 99%